Formulate the concept of a healthy lifestyle in students - G.Tulepova (Proceedings of The ICECRS, 2019)
This paper investigates major points of the formulate the concept of a healthy lifestyle in students. Therefore, one of the important tasks of improving the health of the people is mentioned from different points. Concern about the health of the younger generation in the country is on the level of state policy. All of this requires knowledge of the main factors that affect the health of the younger generation, the creation of methodological, psychological, pedagogical, medical and hygienic foundations for the formation of healthy lifestyles for students.